Persepsi Ibu Rumah Tangga terhadap Pendidikan Kesehatan Reproduksi bagi Remaja (Studi Kasus Pada Kelompok BKR Kecamatan Prambanan Kabupaten Sleman) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
Background: Recently various adolescents' behavior is very worried in our society. Indeed, unprotected sexuality is a very worried problem in the whole of health problem. It is expected that housewives could give reproduction health education in their family, although it is found that from many studies